Acute Diarrhoea in Dengue Patients – A Hospital-based Cross-sectional Study (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Introduction: In Bangladesh, dengue fever is an endemic illness, with high rates of mortality during outbreaks. Acute diarrhoea is a common symptom of dengue fever. This study aimed to identify the frequency of acute diarrhoea in dengue virus infection, and its association with various factors and the in-hospital outcome.Methods: This cross-sectional study involved 203 dengue patients who were admitted to a tertiary-level teaching hospital in Dhaka, Bangladesh, between July and October 2023.  The frequency of acute diarrhoea in dengue patients was calculated, and its associations with various demographic, clinical and haematological parameters, complications, categories of dengue virus infection, ICU/HDU transfer and length of hospital stay were assessed.Results: Diarrhoea developed in 17.7% of dengue patients. The study identified an association of platelet count less than 50,000/cumm with acute diarrhoea in dengue patients (p-value